2013
DOI: 10.5171/2013.956990
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Cytokines in the Saliva, Gingival Crevicular Fluid and Serum of Diabetic Patients with Periodontal Disease

Abstract: Periodontal disease (PD) is a complication of diabetes mellitus (or diabetes). Various proinflammatory cytokines are expressed in the saliva, gingival crevicular fluid (GCF) and serum of diabetic patients with PD. The aim of this study was to review the proinflammatory cytokinees that are expressed in the saliva, GCF and serum of diabetic patients with PD. The addressed focused question was "Which proinflammatory cytokines are expressed in the saliva, GCF and serum of diabetic patients with PD?" Databases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…In this study, IL-1β was examined randomly among Type 1 diabetes mellitus, Type 2 diabetes mellitus and ketoacidotic patients. Plasma levels of IL-1β in patients submitted were higher than control group which is a similar finding to that reported by Javed and Ahmed (2013). In the present study, the mean plasma level of IL-1β was nearly three, seven and five times the control group value in Type 1 diabetes mellitus, ketoacidotic and Type 2 diabetes mellitus patients, respectively.…”
Section: (55%)supporting
confidence: 91%
“…In this study, IL-1β was examined randomly among Type 1 diabetes mellitus, Type 2 diabetes mellitus and ketoacidotic patients. Plasma levels of IL-1β in patients submitted were higher than control group which is a similar finding to that reported by Javed and Ahmed (2013). In the present study, the mean plasma level of IL-1β was nearly three, seven and five times the control group value in Type 1 diabetes mellitus, ketoacidotic and Type 2 diabetes mellitus patients, respectively.…”
Section: (55%)supporting
confidence: 91%
“…The study of Dambala et al in 2017 also showed the same result (43). In the study of Javed et al (2913), the level of MMP-8 was higher in the saliva and serum of patients with PCOS and periodontal disease compared to the control group (comprised of women who were systemically healthy and had healthy gums) (16). However, the results of studies are contradictory (44)(45)(46).…”
Section: Discussionmentioning
confidence: 82%
“…This process is resulted from the imbalance between the periodontal pathogens and the host response (16).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, although all the readings of MMP-9 fall within the normal reference range, they were higher in women with PCOS regardless of their gingival status compared to women from the control group. The possible linkage between MMP-9 and PCOS pathogenesis is that the rate of growth and regeneration of ovarian follicles is modified by the balance between MMPs in the extracellular environment [23], which may explain the higher levels seen in women with PCOS compared to women in the control group in some studies [24][25][26]. Other studies provided contradictory results [27][28][29].…”
Section: Discussionmentioning
confidence: 99%